2006
DOI: 10.1097/01.shk.0000191377.78144.d9
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Liver X Receptor Protects Against Hepatic Injury in Endotoxemia by Suppressing Kupffer Cell Activation

Abstract: Recent reports have demonstrated that liver X receptors (LXRs) of the nuclear receptor family have anti-inflammatory effects on macrophages. Here we examine whether activation of LXR by the synthetic agonist GW3965 can ameliorate the liver injury/dysfunction caused by endotoxins in the rat. Male Wistar rats received GW3965 (0.3 mg/kg) or vehicle (50% dimethyl sulfoxide) 30 min before coadministration of lipopolysaccharide (LPS, 5 mg/kg i.v.) and peptidoglycan (1 mg/kg i.v.). Treatment with GW3965 attenuated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 32 publications
2
67
1
Order By: Relevance
“…Kupffer cells and the sinusoidal endothelial cells are the most abundant nonhepatocyte cells, representing up to 20% and 15% of all liver cells, respectively (45). PPAR␣ is not detected in isolated rat Kupffer cells (58), whereas LXR␣ is highly expressed in these cells (90). It is therefore possible that a minor portion of the detected LXR binding sites originate from Kupffer cells and these sites would not have overlapping LXR and PPAR␣ binding in hepatocytes.…”
Section: Discussionmentioning
confidence: 96%
“…Kupffer cells and the sinusoidal endothelial cells are the most abundant nonhepatocyte cells, representing up to 20% and 15% of all liver cells, respectively (45). PPAR␣ is not detected in isolated rat Kupffer cells (58), whereas LXR␣ is highly expressed in these cells (90). It is therefore possible that a minor portion of the detected LXR binding sites originate from Kupffer cells and these sites would not have overlapping LXR and PPAR␣ binding in hepatocytes.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, activation of LXR was found to protect against hepatic injury in an endotoxemia model (Wang et al, 2006c). LXR was shown to attenuate LPS-induced release of TNF-␣ and PGE 2 in a dose-dependent fashion, suggesting that LXR activation may protect against liver injury by suppressing Kupffer cell activation .…”
Section: Roles For Saturated and Monounsaturated Fatty Acids In Nonalmentioning
confidence: 99%
“…In addition, in vivo and in vitro studies have demonstrated that activation of LXR agonists antagonises inflammatory gene expression in mouse macrophages [10], microglia and astrocytes [11], and human monocytes [12]. In cultured murine and human macrophages the synthetic LXR agonist GW3965 has been shown to reduce cytokine-induced tissue factor (TF) production [13] and we have previously shown that GW3965 dose-dependently attenuated LPS-induced release of TNF-α and prostaglandin E 2 by hepatic Kupffer cells in vitro as well as in vivo [14]. Human islets exposed to human blood trigger an instant blood-mediated inflammatory reaction, characterised by platelet consumption and activation of the coagulation and complement systems, and this activation may impair engraftment after intraportal islet transplantation [15].…”
mentioning
confidence: 99%